Stimulating Political Imagination With Arts-Based Methods: The Case of Utopia Consultation - Perheentupa, Inna; Porkola, Pilvi (Sage, 2024)
In this article, we identify ways to methodologically stimulate political imagination in sociological research by exploring an art concept called ‘utopia consultation’ and related arts-based exercises. We investigate how political imagination can be stimulated and practised through arts-based research methods in sociology, and what tangible tools arts-based research offers for studying the intangible. Our analysis builds on recent work on utopia, understood as a tool rather than a blueprint, and sociology of the future, which focuses on the future as an analytical category. We draw on 18 one-on-one utopia consultation sessions conducted in 3 upper secondary schools in Finland, and 3 facilitated collective discussions with the participants in each education institution to discuss their experiences of the one-on-one utopia consultations. Based on our analysis, we suggest four key methodological practices for stimulating political imagination: dialogue, play, cultivating a hopeful orientation to the not-yet, and collective utopian negotiation. We advance sociological discussions of methodology around utopia and political imagination, and contribute to sociological work on the intangibility of discovering the not-yet through arts-based methods by identifying tangible practices and tools for studying the intangible.
Keywords: taidelähtöiset menetelmät; metodologia; tutkimusmenetelmät; mielikuvitus; sosiologia; yhteiskuntatieteet; utopiat